2020
DOI: 10.1002/eap.2091
|View full text |Cite
|
Sign up to set email alerts
|

Burning savanna for avian species richness and functional diversity

Abstract: Prescribed fire is used throughout fire-prone landscapes to conserve biodiversity. Current best practice in managing savanna systems advocates methods based on the assumption that increased fire-mediated landscape heterogeneity (pyrodiversity) will promote biodiversity. However, considerable knowledge gaps remain in our understanding of how savanna wildlife responds to the composition and configuration of pyrodiverse landscapes. The effects of pyrodiversity on functional diversity have rarely been quantified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Tis could have led to a loss in breeding grounds, food, and cover, thereby restricting birds to the riparian forest and woodland habitats. We also observed higher numbers of post-fre specialists (mostly northern carmine bee-eater and some raptors like grasshoppers and lizard buzzards, among others) and other generalist species, suggesting that many savanna species can tolerate and utilize burned areas [85]. Tough the attraction of generalist species to the burnt site could lead to increase in avian species richness [86], our study found otherwise.…”
Section: Variations In Species and Functional Diversity Measuresmentioning
confidence: 67%
See 1 more Smart Citation
“…Tis could have led to a loss in breeding grounds, food, and cover, thereby restricting birds to the riparian forest and woodland habitats. We also observed higher numbers of post-fre specialists (mostly northern carmine bee-eater and some raptors like grasshoppers and lizard buzzards, among others) and other generalist species, suggesting that many savanna species can tolerate and utilize burned areas [85]. Tough the attraction of generalist species to the burnt site could lead to increase in avian species richness [86], our study found otherwise.…”
Section: Variations In Species and Functional Diversity Measuresmentioning
confidence: 67%
“…Tough the attraction of generalist species to the burnt site could lead to increase in avian species richness [86], our study found otherwise. In contrast, Docherty et al [85] found a positive association between species richness and newly burned habitats in the Pilanesberg National Park, South Africa [85].…”
Section: Variations In Species and Functional Diversity Measuresmentioning
confidence: 90%
“…With several years of added experience, fire managers may be able to use these models to fine-tune the outcome a prescribed fire is likely to have on groundforaging species. Greater post-burn heterogeneity and the type and configuration of fire patches promote avian diversity in other fire-maintained systems (Docherty et al, 2020).…”
Section: Ignition and Weathermentioning
confidence: 99%
“…However, these agricultural policies have been proved rather ine cient, especially in Southern European countries, which highlights the need for a greener EU farm policy (Pe'er et al The complex interactions between re and vegetation dynamics make their impacts on biodiversity hardto-predict, especially under alternative land-use and/or re-suppression policies. Previous studies have found that policies promoting HNV farmlands can be effective solutions for biodiversity conservation and wild re mitigation in areas largely affected by land abandonment (Aquilué et Species richness has been widely used as a measure of biodiversity and its response to different environmental factors, such as land-use change and re effects (Docherty et al 2020). Nonetheless, the importance of measuring the effects of ecological disturbances on functional diversity has been progressively mentioned as pivotal to assess the impacts on the distribution and abundance of species traits that contribute to the community resilience and ecosystem functioning (Wood et al 2015;Riemann et al 2017).…”
Section: Introductionmentioning
confidence: 99%